Chemical Composition and Bioactive Compounds in Bananas and Postharvest Alterations - Guiné, Raquel (2017)
Bananas arise as one of the most popular fruits consumed all around the world. Banana belongs to the genus Musa from the family Musaceae. It is original from tropical regions and presents a strong ability to protect itself from the oxidative stress caused by extreme climatic conditions such as intense sunshine and high temperature. For this protection, bananas increase the production of bioactive compounds with antioxidant activity, which protect the fruit from the oxidative damage. Scientific studies have demonstrated that bananas (both in the pulp and peel) contain different antioxidant compounds, like vitamins (A, B, C and E), β-carotene and phenolic compounds (catechin, epicatechin, lignin, tannins, anthocyanins). Furthermore, banana is also notably rich in minerals, like potassium and phosphorus. The knowledge about the chemical composition and the contents in compounds with biological activity is of high interest given the importance of bananas as a valuable food all over the world. However, because bananas are perishable due to some factors like chemical reactions, including those that result in the production of ethylene, their postharvest conservation in pivotal for the commercialization. The effects of postharvest treatments and storage conditions on the composition of bananas are, therefore, essential. In this way, the present chapter focus on the composition of bananas, including macronutrients, micronutrients and bioactive compounds, as well as the effect of postharvest treatments and storage conditions in the quality of bananas.